(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
ecommissioning is the final stage of the life of a platform located offshore in order to support the decommissioning activities that will be carried out, a modified barge is designed to become a tool that can assist the dismantling of offshore platforms. The modification made is by adding an appending frame whose function is to lift the platform that is ready to be dismantled. Of course, not only that is a consideration in the modification of the decommissioning barge but also the planning of the stowage plan design for the modified barge model so that the components and cargo on the barge can be placed in the appropriate position so that the designed barge has a capacity that matches the purpose of the barge. Then when you have made a stowage plan for the decommissioning barge, the next step will be modeling the barge starting from making the hull to the load and also the tank. When all these parts have been made, validation is carried out to compare the value of the model with that in the stability booklet, if so, the next step is to create a code using the moses executive. Analysis when lifting that has been simulated in this study getting a value with the highest CoG point variation, the farthest and with a draft variation of 4.5m, 5.5m, 5.8m, it is found that the stability value meets the DNVGL-ST-N001 criteria in the GM (metacenter height) value, intact range, area ratio.